Motherhood in Wordsworth: A Psychoanalytic Study of his Poetics - Najim Abid Al-Khafaji, Saad (Al-Adab Journal, 2018)
By definition, the Romantic ego is a male; the creator of language which helps him to establish “rites of passage toward poetic creativity and toward masculine empowerment.”1 The outlet for a male quest of self – possession in Romantic poetry is women. For the Romantic poets , the “true woman was emotional, dependent and gentle –a born flower”2 and “the Ideal mother was expected to be strong , self- reliant , protective and efficient caretaker in relation to children and home.”4 With emphasis on the individual in Romantic literature and ideology, mothers are depicted as good when they are natural or unnaturally bad. In the Romantic period then, women’s maternal function equals the “foundation of her social identity and of her sexual desire.”5 Consequently, “convinced that within the individual and autonomous and forceful agent makes creation possible”, the Romantic poets “struggle to control that agent and manipulate its energy.”6In a number of William Wordsworth’s (1770-1850) poems, this creative agent who possesses the powers of creation and imagination becomes a female character who is also often a mother. Nonetheless, when critics examine mothers in Wordsworth’s poetry, they also explore the child/poet’s relationship. Events in Wordsworth’s life surely influenced his attention to mothers. From a psycho-analytic perspective this interest might be an unconscious desire to resurrect the spirit of his dead mother Ann Wordsworth who died when the poet was almost eight. Thus in his poetry, the mother is the counterpart of the genuine faculty of the imagination of the poet and has a strong and felt presence within the poet’s poetic system.In The Prelude, Wordsworth acknowledges his mother’s deep influence on him. He associates her death with the break within his own poetic development; a sign that the poet relies upon in his creative power .It is through her that the young poet came first in contact with the genial current of the natural world. Nevertheless, without his mother, the male child’s connection to nature not only stands, it grows stronger: